Binding of tea catechins to rice bran protein isolate: Interaction and protective effect during in vitro digestion. (March 2017) - Shi, Meng; Huang, Long-Yue; Nie, Ning; Ye, Jian-Hui; Zheng, Xin-Qiang; Lu, Jian-Liang; Liang, Yue-Rong
Abstract: Rice bran protein isolate (RBPI) was prepared from defatted rice bran and used to deliver tea catechins. RBPI had the high adsorption selectivity for tea catechins over caffeine. The adsorption characteristics of tea catechins onto RBPI were determined over a range of time (0–300 min), concentration (0.25–3.5 g L − 1 ) and temperatures (5 °C, 20 °C and 35 °C). The adsorption kinetic data of EGCg and total catechins (TC) onto RBPI showed excellent fitness with the pseudo-second-order model, indicating that chemisorption is the dominating process. Langmuir and Freundlich models adequately described the isothermal adsorption of tea catechins onto RBPI, and the maximum adsorption of EGCg and TC were achieved at 5 °C. SDS-PAGE profiles indicated that globulin and albumin were the major soluble proteins in RBPI to bind tea catechins. Fourier transforms infrared spectroscopy analysis showed that the protein secondary structures of RBPI were altered upon interaction with catechins, with a great increase in random coil and β-antiparallel, a minor increase in α-helix and a reduction in large loop and turn. Binding tea catechins to RBPI respectively increased the recovery% of EGCg and TC from 10.5% and 17.7% to 29.5% and 31.6% after in vitro intestinal digestion. Thus, RBPI is a promising food matrix for delivering tea catechins to gastrointestinal tract. Graphical abstract: Highlights: Rice bran protein isolate selectively incorporates tea catechins over caffeine. SDS-PAGE shows globulin and albumin are soluble proteins to bind catechins. Catechins-binding alters the protein secondary structures of RBPI. RBPI delivering greatly increased the stabilities of catechins in intestinal fluid.